Evaluation of an emergency medicine‐focused clinical pathology training course for non‐clinical pathology house officers. Issue 2 (20th February 2020) - Pavlides, Stavros; Lynch, Alex; Snowden, Khalid; Leissinger, Mary
Abstract: Objective: Determine whether an emergency medicine–focused clinical pathology training course improved the proficiency of house officers. Design: Prospective blinded study. Setting: Veterinary academic center. Study Subject: House officers enrolled in programs other than clinical pathology. Interventions: A 4‐hour curriculum was provided by a board‐certified specialist in veterinary clinical pathology. Measurements and Main Results: A focused clinical pathology lecture course derived from historical teaching materials was delivered. A pre‐ and post‐course multiple choice question examination was taken by the enrolled house officers, as well as a survey regarding their confidence level pre‐ and post‐course utilizing a novel 5‐point scoring system, ranging from 1 (very low confidence) to 5 (very high). A total of 21 house officers completed the study, 5 of which attended didactic lectures, 13 utilized an online learning platform, and 3 used a combination of both. There was a significant improvement in all house officers' post‐training course examination results compared to pre‐course results (pre‐course examination score: mean 49% ±12; post‐course examination score: mean 72.5% ± 15.7; P  < 0.0001). There was a significant difference in pre‐ and post‐course examination scores for each of the 3 topic areas: hematology (pre‐course: mean 47% ±16; post‐course: mean 71% ± 15.8; P ≤ 0.0001); urinalysis (pre‐course: mean 65.7% ± 12.5; post‐course: mean 87.6% ± 22.1; P  = 0.0004); and fluid analysis (pre‐course: mean 37.1% ± 14.1; post‐course: mean 60.5% ± 15; P ≤ 0.0001). There was also a significant increase in the house officers' confidence score in overall clinical pathology skills (pre‐course: mean 2.2 ± 1.5; post‐course: 3.6±1.4; P =  0.0005). Conclusion: This study identified that a 4‐hour clinical pathology training course relevant to small animal emergency medicine improved the knowledge and confidence of nonclinical pathology house officers. A similar training course may prove helpful in the future to improve the proficiency of emergency veterinarians.